MANAJEMEN KESEHATAN DAN KESELAMATAN KERJA GUNA MENINGKATKAN PRODUKTIVITAS KERJA KARYAWAN DALAM PERSPEKTIF EKONOMI ISLAM - Agus Subandono; Dijan Novia Saka (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam IAIN Kediri, 2019)
Health and work safety (K3, Re: Kesehatan dan Keselamatan Kerja) is one of the requirements to improve employee performance, in that K3 is right of each worker and to win free competition. Where health and work safety become one of requirements that should be fulfilled by every company in Indonesia. Therefore effort to improve health and work safety should be priority and commitment for every part either government or private part, from stake holder level to all employees in company management. Ergonomics is a multidisciplinary and interdisciplinary approach that seeks to harmonize tools, techniques and work environments against the capabilities and limitations of the workforce so as to create healthy, comfortable, safe and safe working conditions.In this case ergonomics also seeks to create health and safety for the workforce so that it can increase work productivity. The goal of K3 and ergonomics is almost same that is to create health and safetywork. Therefore K3 and ergonomics need to be applied in the workplace to improve health and safety work for employee in order to increase employee’s productivity.However, the implementation of K3 and ergonomics in companies, especially in small and medium- companies is still far from what is expected. K3 and ergonomic programs often have low and final priorities for company management. Health and work safety is not everything, but it cannot be denied that without health and safety everything does not mean anything to a company.In that health and work safety is the main principal for employees at work which will certainly affect their performance in the company.